Financial literacy education neoliberalism, the consumer and the citizen - Arthur, Chris. (Educational futures, rethinking theory and practice, 2012)
Consumer financial literacy education often appears as a helpful, commonsense solution to neoliberalism and the individualization of responsibility for economic risk. However, in financial literacy education: neoliberalism, the consumer and the citizen this particular literacy is argued to be both ineffective and unjust. Socially created poverty, unemployment and economic insecurity require more than individual consumer solutions; they require collective responses by engaged, critical citizens. Utilizing concepts from Marx, Foucault, Bourdieu and Baudrillard this book challenges those who claim that ‘there is no alternative’ to neoliberal insecurity and reduce education to a consumerist training of entrepreneurial consumer-citizens who can continually invest in themselves and the market. Through an analysis of consumer financial literacy education’s present and historical supports, as well as its likely effects, this book argues that the choice before us is not financial illiteracy or financial literacy. Rather, the choice is between subjugation to the requirements of perpetual competition or overcoming alienation, insecurity and exploitation, aims the critical financial literacy education outlined at the end of this book supports. This book will appeal to those interested in understanding the conditions of our freedom in an increasingly fi nancialized world – critical educators, philosophers and sociologists of education and fi nancial literacy researchers.